Nucleosome-depleted chromatin gaps recruit assembly factors for the H3.3 histone variant. - Schneiderman, J.I.; Orsi, G.A.; Hughes, K.T.; Loppin, B.; Ahmad, K. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Most nucleosomes that package eukaryotic DNA are assembled during DNA replication, but chromatin structure is routinely disrupted in active regions of the genome. Replication-independent nucleosome replacement using the H3.3 histone variant efficiently repackages these regions, but how histones are recruited to these sites is unknown. Here, we use an inducible system that produces nucleosome-depleted chromatin at the Hsp70 genes in Drosophila to define steps in the mechanism of nucleosome replacement. We find that the Xnp chromatin remodeler and the Hira histone chaperone independently bind nucleosome-depleted chromatin. Surprisingly, these two factors are only displaced when new nucleosomes are assembled. H3.3 deposition assays reveal that Xnp and Hira are required for efficient nucleosome replacement, and double-mutants are lethal. We propose that Xnp and Hira recognize exposed DNA and serve as a binding platform for the efficient recruitment of H3.3 predeposition complexes to chromatin gaps. These results uncover the mechanisms by which eukaryotic cells actively prevent the exposure of DNA in the nucleus.